Public Service Quality in Administration in Kalidoni Kelurahan Office, Palembang City - Femi Asteriniah (JPAS (Journal of Public Administration Studies), 2022)
The purpose of holding this research is to see the service quality of the Kalidoni Urban Village Office, Palembang City, the supporting and inhibiting factors of service at the Kalidoni Village Office, Palembang City. Quality public service or what is commonly referred to as excellent service is the best service that meets service quality standards. To see the quality of service that is actually perceived by consumers, there are indicators of service quality that lie in the five dimensions of service quality, namely: physical evidence or physical evidence, reliability or reliability, responsiveness or response, assurance or assurance, empathy. Empathy This research uses a qualitative approach with a descriptive level of explanation. Data or information is collected through informant interviews. The type of data used in this study is included in the type of qualitative data obtained from interviews with informants, as well as in documents, documents, journals and other literature relevant to this research. The data techniques used include interviews, observation and documentation. The data analysis technique used in this study is an analysis using an interactive model which includes three components of the analysis, namely reduction, data presentation, and conclusion drawing. The results showed that based on the Tangible dimension (physical evidence), the availability of facilities and infrastructure to support the convenience of services such as waiting rooms, parking lots, toilets, prayer rooms, suggestion boxes, and service counters at the Kalidoni Village Office, Palembang City Based on the dimension of reliability, service procedures are a little indifferent due to improper turnaround time. Based on the dimension of Responsiveness, officers do not give a positive response to community complaints, and there is no follow-up to the criticisms and suggestions submitted. Based on the dimension of Assurance, there is still a delay in the process of completing the services provided that are not in accordance with the existing Standard Operating Procedures (SOP) because there are still people who do not complete the required requirements, so they are required to complete these requirements to be able to continue the procedure. Emphaty dimension (Empathy), the lack of attention given by the officers and the lack of hospitality received by the community are complaints that are often raised by the public.